Biodiversity of uptake hydrogenase systems from legume endosymbiotic bacteria. (1st February 2005) - Brito, B.; Baginsky, C.; Palacios, J.M.; Cabrera, E.; Ruiz-Argüeso, T.; Imperial, J.
Abstract : Uptake hydrogenases in legume endosymbiotic bacteria recycle hydrogen produced during the nitrogen fixation process in legume nodules. Despite the described beneficial effect on plant productivity, the hydrogen oxidation capability is not widespread in the Rhizobiaceae family. Characterization of hydrogenase gene clusters in strains belonging to Rhizobium, Bradyrhizobium and Azorhizobium reveals a similar overall genetic organization along with important differences in gene regulation. In addition, phylogenetic analysis of hup genes indicates distinct evolutionary origins for hydrogenase genes in Rhizobia.